Trajectories in long-term condition accumulation and mortality in older adults: a group-based trajectory modelling approach using the English Longitudinal Study of Ageing - Beth Stuart; Andrew Farmer; Nusrat Khan; Hajira Dambha-Miller; Nazrul Islam; Christos V Chalitsios; Yvonne Nartey; Glenn Simpson; Cornelia Santoso (BMJ Open)
Objectives To classify older adults into clusters based on accumulating long-term conditions (LTC) as trajectories, characterise clusters and quantify their associations with all-cause mortality.Design We conducted a longitudinal study using the English Longitudinal Study of Ageing over 9 years (n=15 091 aged 50 years and older). Group-based trajectory modelling was used to classify people into clusters based on accumulating LTC over time. Derived clusters were used to quantify the associations between trajectory memberships, sociodemographic characteristics and all-cause mortality by conducting regression models.Results Five distinct clusters of accumulating LTC trajectories were identified and characterised as: ‘no LTC’ (18.57%), ‘single LTC’ (31.21%), ‘evolving multimorbidity’ (25.82%), ‘moderate multimorbidity’ (17.12%) and ‘high multimorbidity’ (7.27%). Increasing age was consistently associated with a larger number of LTCs. Ethnic minorities (adjusted OR=2.04; 95% CI 1.40 to 3.00) were associated with the ‘high multimorbidity’ cluster. Higher education and paid employment were associated with a lower likelihood of progression over time towards an increased number of LTCs. All the clusters had higher all-cause mortality than the ‘no LTC’ cluster.Conclusions The development of multimorbidity in the number of conditions over time follows distinct trajectories. These are determined by non-modifiable (age, ethnicity) and modifiable factors (education and employment). Stratifying risk through clustering will enable practitioners to identify older adults with a higher likelihood of worsening LTC over time to tailor effective interventions to prevent mortality.